EXPERIMENTAL PRACTICES BY PRINTMAKERS IN THE WORLD OF PRINTMAKING - Hajare, Dr. Sachin Ramrao (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Printmaking (Chhapa Kala) has evolved beyond paper-based prints and has encompassed a broader spectrum of artistic expressions. The world of printmaking witnesses the innovative experiments of numerous artists today, each contributing their unique endeavors. Printmakers are no longer confined by strict rules and are embracing a more versatile and expressive form of printmaking. Today's printmakers are taking a step forward and are diligently working in the realm of printmaking, progressing beyond the confines of traditional printmaking. Printmakers are exploring different mediums with enthusiasm, uncovering new possibilities, and pushing the boundaries of what printmaking can achieve. The traditional distinctions between established, conventional, and unconventional printmaking are being blurred, allowing for a more dynamic and liberated interpretation of the art form. In actuality, the term 'printmaking' itself is undergoing a redefinition, with new rules being formulated. It appears that, in today's artistic landscape, there is a growing recognition of the need to reconsider established norms and rules in printmaking. Research in this context has been extensively conducted, analyzing the various aspects and techniques involved. This study delves into the realm of Chhapa Kala, exploring its widespread influence and its integration into the broader world of art."